Respostas
respondido por:
27
(2x+3)^2-9=12x
2x^2+2.2x.3+3^2-9=12x
2x^2+12x+9-9=12x
2x^2+12x-12x+9-9
2x^2=0
x^2=0/2
x^2=0
x= raiz de 0
x= 0
2x^2+2.2x.3+3^2-9=12x
2x^2+12x+9-9=12x
2x^2+12x-12x+9-9
2x^2=0
x^2=0/2
x^2=0
x= raiz de 0
x= 0
respondido por:
16
(2x+3)²-9=12x
4x^2 + 6x + 6x + 9 - 9 - 12x = 0
4x^2 = 0
x^2 = 0/4
x = +- √ 0/4
x = +- 0
S = { 0 }
4x^2 + 6x + 6x + 9 - 9 - 12x = 0
4x^2 = 0
x^2 = 0/4
x = +- √ 0/4
x = +- 0
S = { 0 }
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás